Efficacy of novel endoscopic hemostatic agent for bleeding control and prevention: Results from a prospective, multicenter national registry - Maselli, Roberta; Da Rio, Leonardo; Manno, Mauro; Soriani, Paola; Andrisani, Gianluca; Di Matteo, Francesco Maria; Fabbri, Carlo; Sbrancia, Monica; Binda, Cecilia; Panarese, Alba; D'Abramo, Fulvio; Staiano, Teresa; Rizza, Stefano; Cannizzaro, Renato; Maiero, Stefania; Stigliano, Vittoria; de Nucci, Germana; Manes, Gianpiero; Sacco, Marco; Facciorusso, Antonio; Hassan, Cesare; Repici, Alessandro (Endoscopy International Open, 2024)
Background and study aims Topical hemostatic agents emerged as a new treatment modality for gastrointestinal bleeding. The aim of this study was to assess the safety and efficacy of PuraStat for control of active bleeding and for prevention of bleeding after different operative endoscopy procedures.Patients and methods A national, multicenter, observational registry was established to collect data from ten Italian centers from June 2021 to February 2023. Demographics, type of application (active gastrointestinal bleeding or prevention after endoscopic procedures, site, amount of gel used, completeness of coverage of the treated area), outcomes (rates of intraprocedural hemostasis and bleeding events during 30-day follow-up), and adverse events (AEs) were prospectively analyzed.Results Four hundred and one patients were treated for active gastrointestinal bleeding or as a preventive measure after different types of operative endoscopy procedures. Ninety-one treatments for active bleeding and 310 preventive applications were included. In 174 of 401 cases (43.4%), PuraStat was the primary treatment modality. Complete coverage was possible in 330 of 401 (82.3%) with difficulty in application in seven of 401 cases (1.7%). Hemostasis of active bleedings was achieved in 90 of 91 patients (98.9%). In 30-day follow-up 3.9% patients in whom PuraStat was used for prophylaxis had a bleeding event compared with 7.7% after hemostasis. No AEs related to the use of PuraStat were reported.Conclusions PuraStat is a safe and effective hemostat both for bleeding control and for bleeding prevention after different operative endoscopy procedures. Our results suggest that the possible applications for the use of PuraStat may be wider compared with current indications.
Keywords: Endoscopy Upper GI Tract; Non-variceal bleeding; Endoscopy Lower GI Tract; Lower GI bleeding; Quality and logistical aspects; Performance and complications; Endoscopic resection (ESD, EMRc, ...); Endoscopic resection (polypectomy, ESD, EMRc, ...)